2021
DOI: 10.1128/spectrum.00955-21
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuous Smooth and White Egg-Shaped Sulfur Structures on a Deep-Sea Hydrothermal Vent Formed by Sulfide-Oxidizing Bacteria

Abstract: At the deep-sea Guaymas Basin hydrothermal vent system, sulfide-rich hydrothermal fluids mix with oxygenated seawater, thereby providing a habitat for microbial sulfur oxidation. Microbial sulfur oxidation in the deep sea involves a variety of organisms and processes and can result in the excretion of elemental sulfur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…In the present study, 16S miTags were used to reveal the prokaryotic community structure in the water column inside the YBH. The relatives of the main OTUs of Desulfatiglandales, Thiomicrospirales, Campylobacterales and Alteromonadales are sulfur-reducing bacteria ( Desulfatiglans ) ( Cifuentes et al, 2021 ; Li et al, 2021 ; Xu et al, 2022 ), sulfur-oxidizing bacteria ( Thiomicrorhabdus , Arcobacter ) ( Magnuson et al, 2021 ; Scott et al, 2018 ; van Erk et al, 2021 ), and Alteromonas , which confirms the metabolic potentials using their classification against SILVA database at order level ( Fig. 5 ).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In the present study, 16S miTags were used to reveal the prokaryotic community structure in the water column inside the YBH. The relatives of the main OTUs of Desulfatiglandales, Thiomicrospirales, Campylobacterales and Alteromonadales are sulfur-reducing bacteria ( Desulfatiglans ) ( Cifuentes et al, 2021 ; Li et al, 2021 ; Xu et al, 2022 ), sulfur-oxidizing bacteria ( Thiomicrorhabdus , Arcobacter ) ( Magnuson et al, 2021 ; Scott et al, 2018 ; van Erk et al, 2021 ), and Alteromonas , which confirms the metabolic potentials using their classification against SILVA database at order level ( Fig. 5 ).…”
Section: Discussionsupporting
confidence: 68%
“…However, Alteromonas can probably grow rapidly when a stronger electron acceptor, oxygen, is available during water filtration onboard under a higher temperature ( Bowman & McMeekin, 2015 ). In previous studies, Arcobacter species belonging to this family occupied the dominant position in the anoxic water column of YBH at depths of 100–150 m ( He et al, 2020 ; Zhang et al, 2021 ) and they have been reported to be able to participate in sulfur cycling as a sulfur oxidizer ( Callbeck et al, 2019 ; van Erk et al, 2021 ). However, sulfur oxidation mainly occurs in the oxic layer or the hypoxic layer, and the anoxic layer mainly performs sulfate reduction and denitrification ( He et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%